2018
DOI: 10.1016/j.jaac.2018.06.024
|View full text |Cite
|
Sign up to set email alerts
|

Increased Risk for Neurodevelopmental Disorders in Children With Orofacial Clefts

Abstract: Objective: Children with orofacial clefts (OFC) may have an increased risk of poor mental health. This study aimed to investigate the risk of psychiatric diagnoses in individuals with OFC, stratified by cleft type. Method: A nationwide register-based cohort of all individuals born with nonsyndromic OFC in Sweden between 1973 and 2012 (n ¼ 7,842) was compared to a matched cohort (n ¼ 78,409) as well as to their unaffected siblings (n ¼ 9,637). The risk of psychiatric diagnoses, suicide attempts, and suicides wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
41
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 40 publications
5
41
2
1
Order By: Relevance
“…Statistically significant impairments in other domains of cognition were also found, but the data did not meet the criteria for study homogeneity and publication bias [15]. Two large Scandinavian population-based studies found that there was a higher risk of being diagnosed with a psychiatric disorder in nonsyndromic patients with clefts compared with individuals without clefts [30,31] and compared with the patients' siblings [31].…”
Section: Introductionmentioning
confidence: 99%
“…Statistically significant impairments in other domains of cognition were also found, but the data did not meet the criteria for study homogeneity and publication bias [15]. Two large Scandinavian population-based studies found that there was a higher risk of being diagnosed with a psychiatric disorder in nonsyndromic patients with clefts compared with individuals without clefts [30,31] and compared with the patients' siblings [31].…”
Section: Introductionmentioning
confidence: 99%
“…) and an increased risk of neurodevelopmental disorders (Tillman et al . ). This variability presents a challenge when designing assessment protocols, in particular the selection of speech samples and the parameters of speech which can be assessed reliably.…”
Section: Introductionmentioning
confidence: 97%
“…As such, 3-year-old children can be highly variable in how they present in these areas despite being within normal developmental limits. Furthermore, variability in presentation can also result from the known delay in expressive language and speech (Cavalheiro et al 2019) and an increased risk of neurodevelopmental disorders (Tillman et al 2018). This variability presents a challenge when designing assessment protocols, in particular the selection of speech samples and the parameters of speech which can be assessed reliably.…”
Section: Introductionmentioning
confidence: 99%
“… 1 Patients with CLP have higher rates of health complications such as speech delays, behavioral disorders, failure to thrive, otitis, hearing loss, and dental anomalies, for which they undergo numerous surgical procedures. 2 4 Although operative treatment has been proven to be beneficial for these patients, there are increasing concerns about higher exposure to general anesthesia and its association with abnormal neurocognitive development. 5 …”
Section: Introductionmentioning
confidence: 99%